2018
DOI: 10.3892/ol.2018.8049
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-302a inhibits osteosarcoma cell migration and invasion by directly targeting IGF-1R

Abstract: Osteosarcoma is one of the most frequent types of primary malignant bone neoplasm in children and adolescents. Despite advancements developed in therapeutic modalities, the 5-year overall survival rates for patients with metastatic osteosarcoma disease remain poor. The present study aimed to investigate the expression level of microRNA-302a (miR-302a) in osteosarcoma tissues and cell lines, and the biological roles of miR-302a in osteosarcoma cells. In addition, the molecular mechanism underlying its tumor sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…We also explored the mechanisms underlining the anti‐tumor effects after targeting mutant TP53. The IGF‐1R signaling pathway plays a significant role in tumor proliferation, growth, and migration in osteosarcomas . Down regulation of IGF‐1R may be one aspect of the mechanism underlining the inhibition of proliferation, colony formation, and migration arising after targeting mutant TP53 in this study.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…We also explored the mechanisms underlining the anti‐tumor effects after targeting mutant TP53. The IGF‐1R signaling pathway plays a significant role in tumor proliferation, growth, and migration in osteosarcomas . Down regulation of IGF‐1R may be one aspect of the mechanism underlining the inhibition of proliferation, colony formation, and migration arising after targeting mutant TP53 in this study.…”
Section: Discussionmentioning
confidence: 74%
“…The IGF-1R signaling pathway plays a significant role in tumor proliferation, growth, and migration in osteosarcomas. 25,[35][36][37] Down regulation of IGF-1R may be one aspect of the mechanism underlining the inhibition of proliferation, colony formation, and migration arising after targeting mutant TP53 in this study. Indeed, it has been reported that down regulation of IGF-1R expression is associated with decreased proliferative activity in osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…In specific BC cell lines, some scholars have found that vitamin C can reduce the reprogramming efficiency of the miR‐302/367 cluster by downregulating TET1 gene expression, which reverses the inhibition of cell invasion and proliferation by this cluster . Insulin‐like growth factor‐1R, can be directly targeted by miR‐302a, which plays a tumor suppressor role by inhibiting the invasion and migration of osteosarcoma cells . One recent study indicated that miR‐302‐3p can suppress cervical cancer metastasis through actions on its direct target, defective in DCUN1D1 .…”
Section: Functions and Mechanisms Of Mir‐302 Cluster In Tumor Developmentioning
confidence: 99%